A study on the perception, usage rate and satisfaction of herbal products among customers in the Northern Region / Fatimah Mohd Saman and Mohammad Zaki Ayob - Mohd Saman, Fatimah; Ayob, Mohammad Zaki (Institute of Research, Development and Commercialization (IRDC), 2007)
The use of herbs and herbal products has become widely accepted in most cultures. This trend benefits not only manufacturers and retailers, but the consumers as well in terms of having varied choices. Although herbal product sales have seen strong, growth, the local content for these products is only about ten percent. Herbs such as tongkat ali (eurycoma longifolia), kacip fatimah (Iabisia pumila), pegaga (centella asiatica), serai wangi (cynbotogon nardus), and sena makki (cassia angustifolia) are well known and very much required in the production of herbal products. This research attempts to understand herbal utilization trends in Kedah, Penang, and Perlis.